2011
DOI: 10.1063/1.3643248
|View full text |Cite
|
Sign up to set email alerts
|

Bubble growth by injection of gas into viscous liquids in cylindrical and conical tubes

Abstract: The effect of partial confinement on the shape and volume of bubbles generated by injection of a constant flow rate of gas into a very viscous liquid is studied numerically and experimentally. Numerical solutions of the Stokes equations for the liquid and the evolution equation for the surface of a bubble, and experiments with two different liquids, show that cylindrical and conical walls concentric with a gas injection orifice in the horizontal bottom of the liquid may strongly affect the shape and volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The departure bubble volume was affected by the angle of the cone or the radius of the cylinder. The results confirmed that the departure volume of the vertically elongated bubbles were significantly larger than those of the round bubbles, generated in the absence of walls, where the radius of cylindrical was smaller than six times of the radius of the orifice, or when the angle of the cone was smaller than 30 o [87]. As bubble grew inside a cylinder or a cone filled with liquid, the surrounded liquid moves downward and eventually, the liquid filled the gap after the bubble departure.…”
Section: Dynamics Of Bubble Growthsupporting
confidence: 75%
“…The departure bubble volume was affected by the angle of the cone or the radius of the cylinder. The results confirmed that the departure volume of the vertically elongated bubbles were significantly larger than those of the round bubbles, generated in the absence of walls, where the radius of cylindrical was smaller than six times of the radius of the orifice, or when the angle of the cone was smaller than 30 o [87]. As bubble grew inside a cylinder or a cone filled with liquid, the surrounded liquid moves downward and eventually, the liquid filled the gap after the bubble departure.…”
Section: Dynamics Of Bubble Growthsupporting
confidence: 75%
“…As was mentioned above, here we shall use a single capillary tube for foam generation in thin and long pipes in order to control the uniformity of bubble sizes. It has been demonstrated that if the ratio of the diameter of the pipe (containing the liquid) over the diameter of the capillary tube (through which the gas is injected) is large, then the effects of the wall on the shape and size of the emerging bubbles is almost negligible [17]. In this context, an important parameter to characterize the foam formation is the so-called Bikerman's unit of foaminess, which is defined by the relation…”
Section: Measurable Foam Propertiesmentioning
confidence: 99%
“…As was mentioned above, here we shall use a single capillary tube for foam generation in vertical pipes with length over diameter ratios in the interval 25 ≤ h/D ≤ 80, as shown in the last column of Table 1, in order to control the uniformity of bubble sizes. It has been demonstrated that if the ratio of the diameter of the pipe (containing the liquid) over the diameter of the capillary tube (through which the gas is injected) is large, then the effects of the wall on the shape and size of the emerging bubbles is almost negligible [18]. In this context, an important parameter to characterize the foam formation is the so-called Bikerman's unit of foaminess, which is defined by the relation…”
Section: Measurable Foam Propertiesmentioning
confidence: 99%